Исследование хромосомных маркеров сортов рапса российской и белорусской селекции - Земцова, Л.В.; Амосова, А.В.; Саматадзе, Т.Е.; Грушецкая, З.Е.; Воловик, В.Т.; Зеленин, А.В.; Лемеш, В.А.; Муравенко, О.В. (Фактори експериментальної еволюції організмів, 2013)
Aims. Dependable marking of rape chromosomes is necessary for breeding of agriculturally important varieties. Using chromosome markers the karyotypes of 13 spring and winter rape varieties of Russian and Belorussian selection were studied. Methods. C-, DAPI-banding and FISH with 26S and 5S rDNA were used. Results. More informative C/DAPI-banding was obtained by using DNA intercalator 9-aminoacridine, and rape chromosome identification was made. 26S and 5S rDNA loci were localized on chromosomes 4, 5, 6, 8, 10, 14, 15, 16 and 18. Intra- and intervarietal polymorphism of these chromosome markers was found. Conclusions. The generalized species karyogram that included all the alternates of C/DAPI-patterns as well as 26S and 5S rDNA localization was constructed.